Cupriavidus pauculus bacteremia related to parenteral nutrition. Case series report - L.F. Valdés-Corona; I. Maulen-Radovan; F. Videgaray-Ortega (IDCases, 2021)
Cupriavidus pauculus is a Gram negative rod that is usually isolated in water and has been extraordinarily isolated in patients with vascular access and / or immunosuppression. In this work we present a series of cases of patients with positive blood cultures for cupríavidus pauculus, during a short period of time in our hospital center. The only characteristic related to all cases was the use of parenteral nutrition. It highlights the rareness of the microorganism and the susceptibility identified in the antibiogram, which may be useful for future cases.